Image Searching within Another Image Using Image Matching and Genetic Algorithms - Kadir Kavaklıoğlu; Mehmet Karakoc (Pamukkale University Journal of Engineering Sciences, 2015)
Main focus of this work is to realize image searching within another image in an efficient way. Image searching within another image is accomplished through the integrated use of image matching techniques and searching algorithms. Artificial neural networks along with various image features such as average color value, color standard deviation, correlation and edge parameters are used for image matching whereas genetic algorithms were used for image searching. In the work presented in this paper, an integrated method based on smart searching algorithms, quick image matching methods and parallel programming techniques were proposed and implemented. Proposed method was tested on several low and high-resolution reference and template images. Results revealed that the proposed method can successfully match images and significantly reduce the total search time.